CONTROL: A randomized phase 2 study of obeticholic acid and atorvastatin on lipoproteins in nonalcoholic steatohepatitis patients. (10th September 2019) - Pockros, Paul J.; Fuchs, Michael; Freilich, Bradley; Schiff, Eugene; Kohli, Anita; Lawitz, Eric J.; Hellstern, Paul A.; Owens‐Grillo, Janet; Van Biene, Courtney; Shringarpure, Reshma; MacConell, Leigh; Shapiro, David; et al.
Abstract: Background & Aims: Nonalcoholic steatohepatitis (NASH) is a chronic and severe form of nonalcoholic fatty liver disease that can progress to cirrhosis and hepatocellular carcinoma and is a risk factor for cardiovascular disease. Although NASH has no approved treatments, obeticholic acid (OCA), a synthetic bile acid and farnesoid X receptor (FXR) agonist, was shown to improve histological features of NASH and fibrosis. Considering that FXR activation influences plasma lipoprotein concentrations, the Combination OCA aNd sTatins for monitoRing Of Lipids (CONTROL) study evaluated how statins can regulate lipoprotein metabolism with OCA treatment in patients with NASH. Methods: This randomized, double‐blind, placebo‐controlled, phase 2 study began with a 5‐week screening/statin washout; 84 patients with NASH were randomly assigned (1:1:1:1) to receive placebo or 5 mg, 10 mg or 25 mg OCA once daily during the 16‐week double‐blind phase. Concurrent once daily atorvastatin (10 mg/days) was initiated at Week 4 with subsequent titration. Enrolled patients had biopsy‐confirmed diagnosis of NASH with no evidence of hepatic decompensation. Plasma was collected to analyse lipoprotein parameters. Results: At Week 4, all OCA groups had an increase from baseline in mean low‐density lipoprotein cholesterol (LDLc) and mean LDL particle concentration (LDLpc), mostly owing to large, less atherogenic LDLc particles. Atorvastatin 10 mg decreased LDLc and LDLpc levels below baseline in all OCA groups by Week 8; higher doses did not provide additional clinical benefits. Conclusions: The CONTROL study showed that OCA‐induced increases in LDLc in patients with NASH were mitigated with atorvastatin. The combination of OCA and atorvastatin was generally safe and well tolerated (NCT02633956).